EFEKTIVITAS MODEL COOPERATIVE LEARNING TERHADAP KEMAMPUAN MEMBACA SISWA KELAS II SD NEGERI SIDOMUKTI 02 - Hanifah Risti Adisti Setyowati; Waskito Aji; Muhammad (STKIP Subang, 2026)
This study aims to analyze the effect of implementing the Cooperative Learning model on the reading skills of second-grade students at Sidomukti 02 Elementary School. The study used a quantitative approach with a pre-experimental design of the One Group Pretest–Posttest Design. The study subjects consisted of 20 second-grade students. Data collection was carried out through reading ability tests, including reading aloud and reading comprehension tests. Data were analyzed using descriptive statistics and paired sample t-tests. The results showed that the average student reading ability increased from 58.20 in the pretest to 82.40 in the posttest. The results of the paired sample t-test showed a significant value between the pretest and posttest scores (p=0.000<0.05), indicating a significant difference between students' reading abilities before and after the treatment. Thus, it can be concluded that the Cooperative Learning model has a significant effect on improving the reading abilities of second-grade students at Sidomukti 02 Elementary School